HUKUM PERMINTAAN DAN PENAWARAN PADA HARGA SAHAM SEKTOR PROPERTI - Amanda; Herlinda Maya Kumala Sari; Detak Prapanca (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the impact of profitability, liquidity, and corporate growth on stock prices in the property sector listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. This study applies a quantitative approach through secondary data processed with Eviews analysis software. Sample selection was carried out using a purposive sampling technique on 23 corporations from a total population of 156. The results show that profitability has a negative and significant effect on stock prices, indicating that profit optimization is not always followed by an increase in stock prices. Conversely, liquidity has a positive and significant effect, indicating a corporation's strong capability in meeting its short-term obligations, which then increases investor confidence. Corporate growth also has a positive and significant effect on stock prices, reflecting that increased business expansion and financial performance can increase investor interest.